Virtual diplomas: Indian software firms catch on-line education wave. - Mitra, Pramit (Far Eastern Economic Review, 1998)
The writer discusses the growing popularity of the concept of online education among software companies in India. It is anticipated that over 20,000 people in India will earn diplomas in computing over the next year without having to leave the comfort of their homes or offices. The idea of online education has already taken hold in countries such as the U.S. and Britain, and now, as it catches on in India, it may have a significant impact on the way that businesses of all kinds operate. This is especially the case for the software development industry, where the need for more and better-trained professionals outstrips the number of qualified candidates by five to one.